The link between relational benefit to relationship quality in priority banking services in Indonesia - Syafrizal, .; Nabsiah, Abdul Wahid; Ishak, Ismail (KnE Social Sciences, 2019)
Relational benefit has an important role in improving relationship quality in a consumer services company, particularly in credence service. However, there are only a few research on the link between relational benefit and relationship quality, especially in credence service like priority banking services. The objective of this study is to fulfill this gap by investigating the links of relational benefit on satisfaction and trust. A survey questionnaire was run to 338 priority banking customers in Jakarta. This study found that functional benefit has a significant influence on relationship satisfaction and trust, while social benefit also has a significant influence on satisfaction and trust. The findings imply that service providers like bankers need to consider the functional benefit and social benefit as it directly affects their customer’s relationship satisfaction and trust. The result of this research is crucial when the intended customer is an important segment like the priority customers who have large deposits and investment products in the banks.